The lexicalisation of HAPPINESS in the Malayic varieties of Indonesia - Primahadi Wijaya Rajeg, Gede; Rajeg, I Made (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
This paper explores the lexicalisation of HAPPINESS in the Malayic varieties spoken in the Indonesian archipelago. We specifically investigate (i) the inventory of lexical forms, and the conceptual categories they encode, that refer to the generic concept of HAPPINESS in English, and (ii) how they vary along the quantitative and sociolinguistic dimensions, particularly the regional variation. Our study reveals that HAPPINESS is strongly lexicalised by forms referring to SENANG overall. In addition to this general trend, we also demonstrated that the lexicalisation of HAPPINESS concept can vary, both qualitatively and quantitatively, across the region at a more generic, concept level, and a more specific level of morph types